Education Sector and Corporate Social Responsibility a Study on Private Sector Secondary School of District North & South Delhi (India) - Pankaj Dixit (Fakultas Hukum, Universitas Warmadewa, 2020)
Educational organizations in private sector require strong corporate strategies. In order to get success in the globally competitive environment they must adopt the strategy of Corporate Social Responsibility. This study analyzed corporate social responsibility and its impact on private sector secondary schools in district North & South Delhi. For this purpose primary data were collected through five point Likert’s scale. The questionnaire was fielded to private sector secondary school teachers in order to get data about the impact of corporate social responsibility on performance of secondary schools. The population of the study was 184 registered private sector secondary schools (140 boys and 44 girls) which included 900 teachers (who taught to class 10th students during session 2017-18) in district North & South Delhi. A sample of 280 teachers (140 male and 140 female) in 70 private sector secondary schools (35 for boys and 35 for girls) were selected through equal allocation sampling formula. Mean, Standard Deviation and t-test were applied for analyzing the data. The Pearson’s correlation was used to evaluate the variable effects. The result from the data indicated that all the four aspects of CSR have positive significant impact on the performance of secondary schools.